2018
DOI: 10.1208/s12248-018-0214-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fc-Fused Cocaine Hydrolase for Cocaine Addiction Treatment: Catalytic and Pharmacokinetic Properties

Abstract: Cocaine abuse is a worldwide public health and social problem without a US Food and Drug Administration (FDA)-approved medication. Accelerating cocaine metabolism that produces biologically inactive metabolites by administration of an efficient cocaine hydrolase (CocH) has been recognized as a promising strategy for cocaine abuse treatment. However, the therapeutic effects of CocH are limited by its short biological half-life (e.g., 8 h or shorter in rats). In this study, we designed and prepared a set of Fc-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Currently, potentially more effective cocaine use disorder treatment options are in the pre-clinical and clinical development stage. [ 45 , 46 ] These treatments are based on accelerating cocaine metabolism by administering a cocaine hydrolase (CocH) [ 45 ]. This cocaine-metabolizing enzyme is able to rapidly reverse cocaine toxicity and has already been tested in rats [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, potentially more effective cocaine use disorder treatment options are in the pre-clinical and clinical development stage. [ 45 , 46 ] These treatments are based on accelerating cocaine metabolism by administering a cocaine hydrolase (CocH) [ 45 ]. This cocaine-metabolizing enzyme is able to rapidly reverse cocaine toxicity and has already been tested in rats [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…2), which is consistent with the expected dimeric structure with disulfide bonds formed on the Fc part. CocH3, which was produced predominantly in a tetramer form in our previous study [9] has a k cat of 5700 min −1 ; however, the fusion protein, Fc(M3)-CocH3, which was constructed without any linker in our previous study [32], exhibited only ~30% catalytic activity against cocaine as compared to the corresponding unfused CocH3.…”
Section: Optimization Of Fc-fused Coch3 Entity With a Linkermentioning
confidence: 85%
“…Q5 ® Site-Directed Mutagenesis Kit was used to introduce each linker between Fc(M3) and CocH3. The pCMV-Fc(M3)-CocH3, constructed in our previous study [32] to encode Nterminal Fc-fused CocH3 without a linker, was used as the template. PCR reactions with Q5 hot start high-fidelity DNA polymerase along with primers listed in Table 1 were utilized to create insertions.…”
Section: Preparation Of Gene Fusion Constructs In Pcmv-mcsmentioning
confidence: 99%
See 1 more Smart Citation
“…The locomotor data are plotted as the mean ± SEM metres travelled in 5-min bin during locomotor activity for 7 h. Particularly for the lethal dose (60 mg/kg), in addition to the hyperactivity, 60-mg/kg cocaine induced convulsion in six out of eight rats, with two rats died after convulsion, 37 Particularly for treatment of cocaine abuse, previous studies 20,23,30,37,41,43 demonstrated that an exogenous CocH (known as a BChE mutant with at least 1000-fold improved catalytic efficiency against cocaine compared to wild-type BChE) can powerfully rescue rats by rapidly detoxifying cocaine and its toxic metabolites 25,27,29,44 at any time point as long as rats are still alive, and also effectively block cocaine-induced hyperactivity. 23,28,30,37,45 However, it was unknown whether an enzyme can also effectively block cocaine-induced DAT trafficking to plasma membrane. According to the animal data with CocH3-Fc(M3) treatment, the enzyme is capable of effectively preventing cocaine from reaching the brain and limiting the brain cocaine concentration to be lower than the threshold (2.0 ± 0.8 μg/g) even with a lethal dose of 60-mg/kg cocaine (ip).…”
Section: Discussionmentioning
confidence: 99%